A leitura sob a abordagem da compreensão ativa : uma análise das relações dialógicas entre os artistas Noel Rosa e Wilson Batista - Santos, Maria das Graças Lima dos (2024)
Reading analyzed under the ethical-aesthetic-discursive dimension plays a fundamental role in understanding artistic-literary texts. We adopted this perspective in order to didactically explore the understanding of the musical dialogue between songs by Noel Rosa and Wilson Batista, which generated several discursive clashes. The dialogue between the songs of these two composers, in the 1930s, reflects and refracts the cultural and social context and summons concrete meanings of the utterances based on the understanding of the dialogical relationships around the replicas established between the compositions. In view of this, the research proposes an analysis of dialogical relationships and active understanding based on the contributions of studies by Bakhtin (2015, 2016) and Voloshinov (2017, 2019). In this context, we investigated how the understanding of dialogical relationships in artistic-literary reading practice, under the focus of the metalinguistic analysis proposed by Bakhtin, in conjunction with the proposal for theoretical-methodological didactic transposition of Reading with valued resignification developed by Carvalho (2021- 2023). The combination of these two studies contributes to the work of ethical-aesthetic-discursive analysis of the samba- canção genre of the aforementioned composers. Along this path, we carried out a case study that highlights the application of an artistic-literary reading itinerary with valued resignification aimed at the dialogical relationships between the songs of Noel Rosa and Wilson Batista. We report and analyze the interactions and pedagogical mediations of this didactic proposal carried out in a 9th grade class at a public school, examining the possibilities for developing the formation of the artistic-literary reader. Based on experiences carried out in the classroom, the research presents, at the end, a notebook with the proposal for a reading workshop with samba-canção by Noel Rosa and Wilson Batista aimed at Basic Education teachers.